Randomised controlled prospective study of the use of adhesive elastic tape for the control of hand oedema in patients with a wrist fracture treated in a cast: a study protocol. (February 2022) - Guasconi, Massimo; Riboni, Dania Zilli; Granata, Carlotta; Bolzoni, Marina; Beretta, Maurizio; Mozzarelli, Fabio; Maniscalco, Pietro
Abstract: Background: Wrist fractures are a common occurrence, affecting patients of all ages. Wrist fracture patients often develop oedema and the presence of a cast increases the risk. The use of adhesive elastic tape is indicated for oedema control, but there is no definitive evidence of its effectiveness. This study aims to evaluate the effectiveness of the tape in control of hand oedema in wrist fracture patients with a forearm cast. Methods: We present a study protocol for a randomised controlled trial with blinded data processing. We will apply the tape to the intervention group after cast application, while the control group will receive the standard treatment. We will evaluate the circumference difference between baseline (T0) and the 7-day follow-up (T1) of both the thumb and of the other 4 fingers merged together. We will collect data regarding re-attendance to the Orthopedic Emergency Room due to "intolerance to the plaster cast". Sample size calculations resulted in a required total of 220 participants (110 per group). Ethical approval for the study has been obtained. Discussion: We aim to demonstrate that the use of tape improves the tolerability of the cast by reducing the oedema formation, the feeling of constriction and pain. Trial registration: ClinicalTrial.gov Identifier: NCT04683887.